The success of the university based crowdfunding in light of the university centered entrepreneurial ecosystem development - Tóth-Pajor, Ákos; Hornyák, Miklós; Kuti, Mónika; Bedő, Zsolt (PTE KTK Műhelytanulmányok, 2021)
Universities implement readily available solutions and tools to become more entrepreneurial with the expectation of short-term success. Establishing university based crowdfunding platforms is one example of this phenomenon. While these solutions are easily accessible and implementable it is not understood what factors make these platforms an efficient tool to inspire entrepreneurial activity at higher education institutions. In other words, will there be a large crowd publishing and funding projects on the platform or will it remain an empty online marketplace? To assess this question, we apply the concept of a university centered entrepreneurial ecosystem, UCEE, which enables us to consider the environment of the university holistically. By taking into account the functional attributes of the UCEE concept, we are able to show that the successful implementation of a university based crowdfunding platform is dependent on the completeness of the ecosystem around the university. Thus, we can consider successful university based crowdfunding as a desired output of a complete university centered entrepreneurial ecosystem. Our findings provide valuable insight into the functioning of the entrepreneurial university concept and practice, informing both policy and institutional level decision makers.